2021
DOI: 10.3389/fonc.2021.722624
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Oligosaccharyltransferase Subunit Ribophorin 1 Induces Endoplasmic-Reticulum-Stress-Dependent Cell Apoptosis in Breast Cancer

Abstract: Ribophorin 1 (RPN1) is a major part of Oligosaccharyltransferase (OST) complex, which is vital for the N-linked glycosylation. Though it has been verified that the abnormal glycosylation is closely related to the development of breast cancer, the detail role of RPN1 in breast cancer remains unknown. In this study, we explored the public databases to investigate the relationship between the expression levels of OST subunits and the prognosis of breast cancer. Then, we focused on the function of RPN1 in breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 57 publications
(68 reference statements)
1
15
0
Order By: Relevance
“…The functions of the genes that appear to be common in the BCAP29/31 reciprocal network have also been explored to some extent. Among them, STT3A and STT3B may induce endoplasmic reticulum stress-dependent apoptosis in breast cancer [51], and TMED10 has been shown to act as a biomarker of poor prognosis in HNSC [52], these results suggest that in HNSC, BCAP29/31 may still play a synergistic role at the level of endoplasmic reticulum output and quality control, and have a prognostic situation.…”
Section: Discussionmentioning
confidence: 94%
“…The functions of the genes that appear to be common in the BCAP29/31 reciprocal network have also been explored to some extent. Among them, STT3A and STT3B may induce endoplasmic reticulum stress-dependent apoptosis in breast cancer [51], and TMED10 has been shown to act as a biomarker of poor prognosis in HNSC [52], these results suggest that in HNSC, BCAP29/31 may still play a synergistic role at the level of endoplasmic reticulum output and quality control, and have a prognostic situation.…”
Section: Discussionmentioning
confidence: 94%
“…46 Current studies have shown that the OST complex is involved in the maintenance of the ER homeostasis, and the loss or abnormal function of its composition affects the ER stress state in cells. 15 Wen et al 47 found that the lack of STT3A in human embryonic kidney cells HEK293 caused ER stress and activated the UPR pathway, and Ding et al 48 found that the loss of RPN1, a non-catalytic subunit of the OST complex, caused ER stress-mediated apoptosis in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…N-linked glycosylation is an important protein modi cation in eukaryotic cells, and Nglycosylation is carried out in the lumen of the endoplasmic reticulum through the oligosaccharyltransferase (OST) complex. Since RPN1 is only present in the rough endoplasmic reticulum and promotes N-glycosylation by selecting speci c substrates, there are fewer research results in cancer-related studies [25] .In the SLC family human genome,SLC3A2 is the second largest membrane protein family.SLC3A2 functions by forming a heterodimeric complex with the light subunits LAT1 and LAT2, which primarily have encoded CD98hc, forming an amino acid transport protein [26] .SLC3A2 regulates the mTORC1 pathway and cellular metabolism by regulating LAT1/LAT2 stability and plasma membrane localization, leading to glutamine and leucine uptake [27] .SLC7A11 is a key component of the cystine/glutamate reverse transport system xc-and is essential for cystine uptake, glutathione (GSH) synthesis [28] .…”
Section: Discussionmentioning
confidence: 99%